STUDI ISLAM KLASIK DAN KONTEMPORER (SEBUAH TINJAUAN EPISTIMOLOGI) - abdullah, amin (Jurnal Bestari, 1994)
The phenomoneon of Islamic study development lately seems to be choked. There is a tendency to make sancity in the area of examination. Meanwhile, politically, among the relationship between Islam and state continues to be the polemic and discussion centre among intellectual Moslems or Islamic political scholar from the period of pre-modern, modern even until contemporary (this time). It is because there is no explicit and total explanation from Islamic sources. Responding to the issue, the dialogue of Bestari this time presents DR. Amin Abdullah (the Lecturer of Postgradute Program of IAIN) Syarif Hidayatullah of Jakarta) and DR. Dien Syamsuddin (the former Chairman of PP Pemuda Muhammadiyah).